2003
DOI: 10.1163/15685620360674245
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and metabolism of Ba-alginate-encapsulated hepatocytes with galactosylated chitosan and poly(vinyl alcohol) as extracellular matrices

et al.

Abstract: Lactobionic acid, bearing a beta-galactose group, was coupled with chitosan to provide synthetic extracellular matrices together with poly(vinyl alcohol) (PVA). The hepatocytes encapsulated in Ba-alginate capsules with galactosylated chitosan (GC) and PVA as extracellular matrices showed aggregation morphologies as the incubation time increased. Ba-alginate-encapsulated hepatocytes with GC exhibited a higher metabolic function in albumin secretion compared to those entrapped in Ba-alginate beads and monolayer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…For the greater efficiency and rapidity of hepatocyte spheroid formation, AL capsules are required to be small size, and AL surface is required to be modified with ligands to receptors. Our previous observations using 2 mm diameter beads or capsules were impertinent in mass transport between cell and culture medium, causing low cell viability [21,33], compared with the 350 mm diameter capsules used in this study, indicating that the latter diameter shows the upper diffusion limit. Aggregation started from 3 to 5 days and only 30-40% of plated cells formed spheroids in the 350 mm diameter AL capsule (data not shown).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…For the greater efficiency and rapidity of hepatocyte spheroid formation, AL capsules are required to be small size, and AL surface is required to be modified with ligands to receptors. Our previous observations using 2 mm diameter beads or capsules were impertinent in mass transport between cell and culture medium, causing low cell viability [21,33], compared with the 350 mm diameter capsules used in this study, indicating that the latter diameter shows the upper diffusion limit. Aggregation started from 3 to 5 days and only 30-40% of plated cells formed spheroids in the 350 mm diameter AL capsule (data not shown).…”
Section: Discussioncontrasting
confidence: 48%
“…The albumin secretion rates of 0.1 or 5 mg/ml XG were lower than those of 0.5 mg/ml XG owing to less adhesion of hepatocytes for 0.1 mg/ml XG and reduced cell mobility caused by more viscous core for 5 mg/ml XG. It has already been reported that the mobility of intra-capsular hepatocytes is dependent on the viscosity inside capsules [33,34]. For albumin synthesis, it was reported that 12 g albumin is synthesized and secreted per day in a 70 kg man [35].…”
Section: Article In Pressmentioning
confidence: 99%
“…The use of Trypan Blue exclusion to establish initial viability and the MTT assay to monitor viability and proliferation over time is common in unencapsulated hepatocyte culture (Sandker et al 1993). The MTT assay has been applied to monitor cell viability in cell-polymer constructs (Guo et al 2003;Wang et al 2003;Son et al 2004) but only in a semi-quantitative manner with no standardization to other cell-counting protocols. One study demonstrated the reliability of the MTT assay as a method for cell number estimate in polymer scaffolds for cardiovascular surgery (Zund et al 1999) in the initial cell seeding stage.…”
Section: Introductionmentioning
confidence: 99%
“…There have been reports on use of the MTT assay to assess viability of mouse myleoma cells, insect cells and hepatocytes seeded on polymer scaffolds (Yamaji and Fukuda 1994;Dvir-Ginzberg et al 2003;Yang et al 2003;Son et al 2004) or hepatocytes encapsulated in alginate (Guo et al 2003). Although the MTT assay is an accurate indicator of cell viability and metabolic activity, cell samples are sacrificed to monitor cell growth and function over time.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 1 mg XG/ml was appropriate for HepG2 cells in alginate capsules to maintain their liver-specific functions. The albumin secretion and ammonia elimination rates decreased in the 4 and 6 mg XG/ml groups because of the reduced cell mobility caused by more viscous core for higher concentrations (Guo et al 2003;Klöck et al 1997). However, it is possible that the diameter of alginate capsules limits the liverspecific functions of HepG2 cells.…”
Section: Resultsmentioning
confidence: 97%